Validation of 3-D non-isothermal CFD simulation with experimental results for single-screw hydrogen extruder. (June 2022) - Gupta, Vishal; Gangradey, Ranjana; Mukherjee, Samiran S.; Verma, Shashikant; Dewasi, Avijit; Mishra, J.; Panchal, Paresh; Nayak, Pratik A.
Highlights: Fuelling of the long-pulse fusion reactors with the pellets of solid hydrogen. Non-isothermal CFD simulation of the visco-plastic fluid at the cryogenic temperature. Analysis of Single-Screw Extruder with different Shear Stress Models for solid hydrogen. Study for the design, development and optimization of the screw extruder system. Comparison of simulated and experimental results for the single screw extruder system. Abstract: The single-screw extruder is used for the continuous formation of solid rod of hydrogen ice and its isotopes. The extruded rod, further, requires to be cut into pellets and injected into the magnetically confined, hot plasma for the fuelling of long-pulse fusion reactors. An extruder is capable to produce and continuously supply the pellets at a frequency of 1–40 Hz. The design and development of a solid hydrogen screw-extruder system require a study of the visco-plastic behaviour of solid hydrogen and its effects on the pressure and speed of the extruder. A CFD tool (Polyflow) from ANSYS TM is employed to estimate the characteristics of the pressure developed by the extruder at different rotational speed of the screw. In the simulations, different Shear Stress Models developed by various researchers are implemented and the results of the same are investigated systematically for Single-Screw Hydrogen Extruder. The results obtained from these simulations are validated with the experimental results on single screw extruder from literature.